NOVEL IMMUNOMODULATORY EFFECT OF GRACILARIA VERRUCOSA AND POTAMOGETON PECTINATUS EXTRACTS ON IN VITRO ACTIVATION OF T CELLS : Life Science-Biology - KUMAR, AARAM A.; SINGH MEENA, VIKRAM; CHATTOPADHYAY, SUBHASIS; CS PANIGRAHI, KISHORE (International Journal of Life Science and Pharma Research, 2012)
Plants are a rich source for immunomodulatory substances which are capable of activating or regulating mammalian immune response. Here we have studied the effects of aqueous crude extracts of two weed plants inhabiting the Chilika lake ecosystem of Orissa, India, Gracilaria verrucosa and Potamogeton pectinatus on T cell activation status. Flow cytometric analysis of T cell activation status by analysing cell viability and expression of early activation marker CD69 indicated that crude extracts (CE) of both plants possessed significant immunomodulatory properties. These were associated with spectroscopic analysis of the extracts by nuclear magnetic resonance (NMR) spectroscopy and UV-Visible spectroscopy. From the results, we propose that while both the extracts are immunostimulatory in nature, their higher doses lead to cellular cytotoxicity. However, in low doses, the extracts are found to be activating T cell responses as depicted by elevated CD69 expression on CD3+ T cells. The immunomodulatory effect is apparently related to the presence of carbohydrate moieties in the extracts as suggested by NMR spectral analysis. Further studies are warranted to elucidate the detailed mechanism of action of the extracts and to pin down the exact active components responsible for the activity